Retinal Detachment Present at Birth in an Infant With a Novel CTNNB1 Mutation - Mellen, Phoebe (Ophthalmic surgery, lasers & imaging retina, 2022)
A full-term neonate was diagnosed on birth with a unilateral total retinal detachment. The contralateral eye had extensive fibrovascular proliferation, temporal dragging, and peripheral nonvascularized retina. Genetic testing confirmed a mutation in the CTNNB1 gene, which has been associated with familiar exudative vitreoretinopathy and phenotypic features including intellectual disability and spastic diplegia. This novel mutation and its associated syndrome should be considered as a cause of retinal detachment presenting in the neonatal period. [Ophthalmic Surg Lasers Imaging Retina 2022; 53:403-405.]